Interpreting wage gaps of disabled men: The roles of productivity and discrimination - Simonetta Longhi; Cheti Nicoletti; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2010)
Using the UK Labour Force Survey, we study wage gaps for disabled men after the introduction of the Disability Discrimination Act. We estimate wage gaps at the mean and at different quantiles of the wage distribution, and decompose them into the part explained by differences in workers' and job characteristics, the part that can be ascribed to health-related reduced productivity, and a residual part which we can more confidently interpret as discrimination. For physically disabled workers, most of the wage gap can be attributed to differences in productivity, while for mentally disabled people we find evidence of wage discrimination.
Keywords: J7; J14; J31; C21; 330; wage gap; discrimination; disability; Oaxaca decomposition; Sozialpolitik; Arbeitnehmerschutz; Behinderte Arbeitskräfte; Arbeitsmarktdiskriminierung; Lohndifferenzierung; Großbritannien